Fertility and female employment dynamics in Europe: the effect of using alternative econometric modeling assumptions - Pierre-Carl Michaud; Konstantinos Tatsiramos (Institute for the Study of Labor (IZA), 2008)
We investigate the direct and long-run effects of fertility on employment in Europe estimating dynamic models of labor supply under different assumptions regarding the exogeneity of fertility and modeling assumptions related to initial conditions, unobserved heterogeneity and serial correlation in the error terms. We find overall large direct and long-run effects of giving birth on employment probabilities, and these effects differ considerably across countries. We find that within countries the results are sensitive to the statistical assumption made on initial conditions, the inclusion of serial correlation and the assumption of strict exogeneity of children. However, the pattern across countries is robust to these assumptions. We show that such patterns are largely consistent with prevailing institutional differences related to the flexibility of the labor markets and family policies.
urn:nbn:de:101:1-20081202126
Keywords: C23; 330; Intertemporal labor supply; female employment; fertility; dynamic binary choice models; initial conditions; Fruchtbarkeit; Frauenerwerbstätigkeit; Arbeitsangebot; Zeitpräferenz; Präferenztheorie; Schätzung; EU-Staaten